Evaluation of Knowledge Levels and Attitudes of Intern Dentistry Students and Assistant Dentists About AIDS - Nazli Zeynep Alpaslan Yayli; Yasemin Beliz Önder (Van Tıp Dergisi, 2021)
INTRODUCTION: Acquired immunodeficiency syndrome (AIDS) is an infectious disease that does not have a vaccine and negatively affects the quality of life of patients. In this study, it was aimed to investigate the knowledge levels and attitudes of intern dentistry students (Group 1) and assistant dentists (Group 2) about AIDS. METHODS: Participants who volunteered for this cross-sectional study were distributed a questionnaire consisting of 3 parts (demographic characteristics, AIDS knowledge level and attitude) and multiple choice questions. Chi-square test was used in the statistical analysis. Statistical significance level was accepted as p<0.05. RESULTS: 89 participants (46 female, 43 male), with an average age of 24.26 (+- 2.52) completed the study. The volunteers were distributed to the groups at a rate of 64% (Group 1) and 36% (Group 2). 97.8% of the participants stated that AIDS is a sexually transmitted disease. In the information scale part of the questionnaire, only the answers given to the statement "Coughing of an AIDS patient can transmit the disease" are significantly different between the two groups (p = 0.023). In all attitude scale questions, there was no statistically significant difference between the two groups (p> 0.05). DISCUSSION AND CONCLUSION: Although the results of this study show an acceptable awareness for both groups in terms of recognizing the AIDS and its transmission routes, there are still prejudices in terms of perspective and attitude towards the disease. Educational programs should be planned for physicians and physician candidates to have more information about the disease.